Hubungan Self Control Dengan Etika Pergaulan Siswa Kelas XI SMA Negeri 1 Lubuk Pakam - Ikhsan, Muhammad; Syaimi, Khairina Ulfa; Hutasuhut, Dina Hidayati; Asyah, Nur (Universitas Mathla'ul Anwar Banten, 2025)
This research aims to find out the relationship between self-control and student social ethics. Self-control is an individual's ability to regulate emotions, impulses, and behavior to conform to prevailing norms. Meanwhile, interaction ethics reflect the extent to which students can interact politely and courteously. The research method used in this study is quantitative with a correlational research design. The population in this study consists of all students in grade XI at SMA Negeri 1 Lubuk Pakam for the 2024/2025 academic year, totaling 382 students. The sampling technique used is random sampling. The sample consists of 38 students. The research instruments used were self-control questionnaires and interaction ethics questionnaires, which have been tested for validity and reliability using Cronbach's alpha. The self-control questionnaire achieved a Cronbach's alpha value of 0.872, while the interaction ethics questionnaire scored 0.919. The measurement scale for attitudes, opinions, and perceptions uses a Likert scale. The results of hypothesis testing show that the correlation coefficient (r) is 0.620 and the significance (p) is 0.000 < 0.05, indicating a positive relationship between self-control and social ethics. The coefficient of determination yields an R-squared value of 0.384 and an R value of 0.620, demonstrating that 38% of social ethics is influenced by self-control and 62% by other factors. This study implies the need for self-control so that students can exhibit positive social ethics.